Pharmacological Effects of Lactuca serriola L. in Experimental Model of Gastrointestinal, Respiratory, and Vascular Ailments. (4th April 2013) - Janbaz, Khalid Hussain; Latif, Muhammad Farhaj; Saqib, Fatima; Imran, Imran; Zia-Ul-Haq, M.; De Feo, Vincenzo
Abstract : Lactuca serriola L. has traditionally been used in folkloric medicine to manage respiratory, gastrointestinal, and multiple other ailments. The present study was undertaken to explore the effect of methanol extract of L. serriola on isolated rabbit tissue preparations, that is, jejunum, trachea, and aorta in an attempt to validate its folkloric use in traditional medicine for gastrointestinal, respiratory, and vascular ailments. The application of the methanol extract to isolated rabbit jejunum preparations exhibited concentration-dependent spasmogenic effect (0.03 to 3.0 mg/mL), but interestingly further increase in concentration (5.0 mg/mL) resulted in complete spasmolytic effect. The pretreatment of the tissue preparations with atropine (0.1 μ M) caused the suppression of the contractile response. Moreover, the same extract also caused relaxation of K + -(80 mM) induced spastic contractions of isolated rabbit jejunum preparations (5.0 mg/mL) and shifted the Ca ++ dose response curves towards right at concentration range of 0.3–1.0 mg/mL. Similarly, the extract application to isolated rabbit tracheal preparations relaxed the carbachol-(1 μ M) induced (0.3–1.0 mg/mL) as well as K + -(80 mM) induced contractions (3.0 mg/mL). Furthermore, it relaxed the phenylephrine (1 μ M)-induced contractions in isolated rabbit aorta preparations (3.0 mg/mL) and K + (80 mM)-induced contractions (1.0 mg/mL). These effects were found comparable to that of dicyclomine, as an antagonist of muscarinic receptors as well as a possible Ca ++ channel blocker. The previously mentioned findings may partially justify the folkloric use of Lactuca serriola in the management of conditions pertaining to spasm of intestine, bronchioles, and vasculature.